ANALISIS AKUISISI PERUSAHAAN MIGAS TERHADAP KEPUTUSAN INVESTASI DAN KINERJA KEUANGAN - Yuni Kurniawati; Heikal, Jerry (Jurnal Riset Akuntansi, 2025)
This study analyzes the potential assessment of company acquisitions in the Oil & Gas sector for investment decisions by comparing changes in financial performance segmentation from 2021 to 2022. The method used is K-Means Clustering analysis to classify companies based on indicators such as Net Profit Margin, Return on Equity (ROE), and Debt-to-Equity Ratio (DER). Data from 33 Oil & Gas sector companies were analyzed, revealing that two companies experienced significant performance improvements (PT Ratu Prabu Energi Tbk and PT Sugih Energy Tbk), one company showed a decline in performance (PT Super Energy Tbk), while the remaining 30 companies remained relatively stable. The findings of this study provide insights for investors in determining acquisition strategies, where companies with improved performance indicate good growth potential, while those with declining performance require further evaluation and may become acquisition targets. This research contributes to the financial and investment management literature by offering a comprehensive analysis of changes in financial performance segmentation in the Oil & Gas sector. The findings serve as a valuable reference for decision-makers in formulating more optimal investment strategies.